Bladder cancer targeting nano-drug and preparation method thereof

CN121731499BActive Publication Date: 2026-10-09JIANGSU CANCER HOSPITAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202512053000.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-31
Publication Date
2026-10-09
Estimated Expiration
2045-12-31

AI Technical Summary

Technical Problem

然而,现有纳米体系仍面临多重瓶颈:许多设计侧重于单一的物理增敏或药物递送功能,未能系统整合诊断与治疗;所采用的纳米材料本身生物活性有限,难以响应肿瘤微环境的特异性刺激以实现药物可控释放;更为关键的是,同时具备多重主动靶向、按需释药以及多模态协同治疗功能的智能纳米平台仍较为缺乏

Benefits of technology

(1)本发明通过构建以负载吉西他滨的聚乳酸羟基乙酸共聚物纳米粒为核心、表面共组装两种功能化无机化合物的杂化结构,实现了纳米药物理化性质与靶向功能的精准调控。引入的阳离子脂质使核心纳米粒表面带正电,这不仅显著提高了其与两种带负电功能化合物之间的静电结合力,确保了杂化壳层组装牢固、包覆均匀,从而提升了纳米制剂的整体稳定性;更重要的是,这一设计使得最终纳米药物具有适宜的尺寸与表面特性,有利于在膀胱灌注后延长黏膜滞留时间,促进对肿瘤组织的渗透。更为关键的是,表面组装的两组分别偶联了叶酸与透明质酸,赋予了纳米药物双重主动靶向能力,能够同时识别膀胱癌细胞表面过度表达的叶酸受体与CD44受体,实现了对肿瘤细胞的高选择性识别与结合,从源头上提升了药物的蓄积效率,并大幅降低了对正常尿路上皮细胞的非特异性损伤,为降低化疗毒副作用奠定了材料基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the technical field of biological medicine, and particularly relates to a bladder cancer targeting nano-drug and a preparation method thereof; the drug is constructed by assembling gadolinium-doped zinc-aluminum layered double hydroxide folate conjugate and bismuth-tellurium alloy nanocluster hyaluronic acid complex two functional components on the surface of polylactic acid-glycolic acid copolymer nanoparticles loaded with chemotherapy drug gemcitabine as a core. During preparation, the drug-loaded nanoparticles are prepared by using the multiple emulsion solvent evaporation method, and then the two functional compounds are co-assembled on the surface of the nanoparticles by using electrostatic interaction to form a multifunctional hybrid shell. The nano-drug integrates active targeting, microenvironment response drug release, multi-modal imaging, and multiple functions such as chemotherapy synergistic chemical kinetics treatment and radiotherapy sensitization, can significantly improve the enrichment and penetration of the drug in the bladder tumor site, realize efficient synergistic treatment and reduce systemic toxicity, and is particularly suitable for intravesical perfusion treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical technology, specifically relating to a bladder cancer-targeting nanomedicine and its preparation method. Background Technology

[0002] Bladder cancer, one of the most common malignant tumors of the urinary system, presents a significant challenge to clinical treatment due to its high recurrence rate and progression risk. Currently, for non-muscle-invasive bladder cancer, intravesical instillation therapy following transurethral resection is the standard treatment, with commonly used drugs including chemotherapy agents and immunomodulators. However, traditional instillation therapy has significant limitations: the drug's residence time in the bladder is short, its penetration into tumor tissue is poor, and it lacks selectivity for cancer cells, leading to irritation and damage to normal urothelial cells. Patients often experience adverse reactions such as cystitis, severely affecting treatment adherence and efficacy. Furthermore, the heterogeneity of tumor cells and drug resistance mechanisms limit the effectiveness of single-therapy, necessitating the development of novel drug delivery strategies that can increase local drug concentration, prolong the duration of action, and overcome drug resistance.

[0003] With advancements in nanotechnology and biomaterials science, nanomedicine delivery systems offer novel pathways to improve bladder cancer treatment. Researchers have developed various carriers based on liposomes, polymer nanoparticles, and inorganic nanomaterials, attempting to enhance drug accumulation at tumor sites through passive targeting effects or conjugation of targeting molecules. However, existing nanosystems still face multiple bottlenecks: many designs focus on single physical sensitization or drug delivery functions, failing to systematically integrate diagnosis and treatment; the nanomaterials themselves have limited bioactivity, making it difficult to respond to specific stimuli from the tumor microenvironment to achieve controlled drug release; more critically, intelligent nanoplatforms with multiple active targeting, on-demand drug release, and multimodal synergistic therapy functions are still relatively scarce. For example, while some reported nanoparticles have achieved receptor targeting, they lack adaptability to the complex tumor microenvironment and cannot provide real-time monitoring of the treatment process, resulting in limited efficacy improvement and the inability to achieve personalized treatment adjustments.

[0004] Therefore, developing a nanomedicine capable of simultaneously achieving precise targeting, intelligent drug release, multi-mechanism synergistic therapy, and integrated diagnostic and therapeutic functions has become crucial for overcoming the current challenges in bladder cancer treatment. An ideal nanomedicine should be able to precisely identify bladder cancer cells through multiple targeting ligands, utilize the physicochemical properties of the tumor microenvironment (such as weak acidity and high reducing power) to achieve targeted intelligent drug release, and synergize with multiple mechanisms such as chemotherapy, chemokinetics, and radiosensitization to overcome drug resistance and improve efficacy. Simultaneously, the system should ideally integrate imaging capabilities to provide visual guidance for the treatment process. Against this backdrop, this invention aims to construct a novel multifunctional bladder cancer-targeting nanomedicine that meets all the above requirements, providing clinicians with a more efficient, low-toxicity treatment option with real-time monitoring capabilities. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a bladder cancer-targeting nanomedicine and its preparation method.

[0006] In a first aspect, the present invention provides a method for preparing a bladder cancer-targeting nanomedicine, comprising the steps of: S1. By weight, dissolve 5-15 parts of gemcitabine in deionized water containing 0.5-2.0 parts of poloxamer 188 to obtain an aqueous phase; dissolve 40-60 parts of polylactic acid-glycolic acid copolymer, 2-10 parts of 1,2-distearate-sn-glycerol-3-phosphate ethanolamine-N-[methoxy(polyethylene glycol)-2000], and 1-5 parts of 1,2-dioleoyl-3-trimethylammonium-propane in 1-3 mL of dichloromethane to obtain an oil phase; inject the aqueous phase into the oil phase under ice-water bath conditions and sonicate to obtain a primary emulsion; pour the primary emulsion into an aqueous phase containing 100-300 parts of polyvinyl alcohol and emulsify under stirring to obtain a secondary emulsion; S2. Transfer the double emulsion to a beaker and stir at room temperature to obtain a solidified nanoparticle suspension. Centrifuge the solidified nanoparticle suspension at 2-4°C, collect the precipitate, and wash it with deionized water to obtain gemcitabine-loaded PLGA nanoparticles. Redisperse the gemcitabine-loaded PLGA nanoparticles in Tris-HCl buffer, add 2.5-15 parts of gadolinium-doped zinc-aluminum layered double hydroxide-folic acid conjugate and 2.5-15 parts of bismuth-tellurium alloy nanoclusters-hyaluronic acid complex to obtain a mixture. Incubate the mixture with shaking at room temperature. After incubation, centrifuge to collect the product, wash the product with deionized water to obtain the washed product, and redisperse the washed product in phosphate buffer.

[0007] In this invention, the assembly mechanism of the bladder cancer-targeting nanomedicine follows the sequential principles of "core-shell structure construction" and "electrostatically driven functionalization," with its synergistic effect stemming from the multi-level responses and complementary mechanisms of each component at the targeting, drug release, and therapeutic levels. Assembly begins with the preparation of polylactic-co-glycolic acid nanoparticles loaded with gemcitabine, based on a water-oil-water double emulsification and solvent diffusion process. In the inner aqueous phase, hydrophilic gemcitabine and a stabilizer form a homogeneous solution; when this solution is injected into an organic phase containing polymers and cationic lipids and subjected to high-intensity sonication, a water-in-oil primary emulsion droplet is formed. During this process, cationic lipid molecules are oriented at the oil-water interface, imparting their positive charge properties to the emulsion droplet interface. Subsequently, the primary emulsion is poured into an aqueous solution containing an outer aqueous phase stabilizer and undergoes secondary emulsification to form a water-in-oil-in-water complex emulsion structure. As the organic solvent evaporates and diffuses into the outer aqueous phase, the polymer in the oil phase gradually solidifies and precipitates, encapsulating the inner aqueous phase and its drug within, forming dense solid nanoparticles. The cationic lipids are ultimately embedded on the nanoparticle surface, giving them an overall positive charge. This positive charge provides the crucial electrostatic driving force for the subsequent adsorption and assembly of functional components. The subsequent functionalization assembly mechanism mainly relies on electrostatic adsorption and intermolecular forces. When two negatively charged inorganic functional compounds are co-incubated with positively charged drug-loaded nanoparticles, the strong attraction between the positive and negative charges causes them to rapidly approach and tightly bind together. Simultaneously, the potential hydrophobic interactions between the organic segments in the compounds and the hydrophobic surface of the nanoparticles, as well as possible hydrogen bonding, further stabilize this assembly, ultimately forming a dense, multifunctional hybrid shell around the drug-loaded nanoparticles. The synergistic mechanism of this nanomedicine in vivo is a multi-stage, intelligently responsive cascade process. First, its dual active targeting mechanism significantly enhances the enrichment efficiency at the tumor site: the nanomedicine, through surface folic acid and hyaluronic acid ligands, acts like a dual recognition code, simultaneously locking onto the corresponding overexpressed receptors on the tumor cell membrane, achieving precise anchoring and efficient endocytosis. Once inside the cell, its dual responsive drug release mechanism is sequentially activated: in the weakly acidic environment of the lysosome, the acid-sensitive amide bond connecting folic acid breaks, not only releasing folic acid but also promoting the partial dissociation of the zinc-aluminum layered double hydroxide laminar layer, accelerating gemcitabine release, and simultaneously exposing the gadolinium ion catalytic center to initiate chemokinetic therapy; in the highly reducing environment of the cytoplasm, the disulfide bonds of the hyaluronic acid shell are cleaved by glutathione, and the shell dissociates, exposing the internal bismuth-tellurium alloy nanoclusters, fully preparing them to exert their radiosensitizing function. Ultimately, the multimodal synergistic treatment mechanism produces an additive or even multiplicative anti-tumor effect: gemcitabine acts as the main chemotherapy agent to interfere with DNA synthesis; hydroxyl radicals catalyzed by gadolinium ions induce intracellular oxidative stress, resulting in chemokinetic therapy; and exposed bismuth-tellurium alloy nanoclusters can locally enhance the radiation dose under external radiation irradiation and may assist in killing cells through photothermal effects.These three treatment mechanisms attack tumor cells through different pathways, promoting each other and effectively overcoming the drug resistance problem of single therapy, thus achieving a synergistic therapeutic effect greater than the sum of its parts.

[0008] According to a preferred embodiment of the present invention, in step S1, the emulsification time under stirring is 2-4 minutes.

[0009] According to a preferred embodiment of the present invention, in step S2, the mixture is incubated by shaking at room temperature for 12-14 hours.

[0010] According to a preferred embodiment of the present invention, the preparation method of the gadolinium-doped zinc-aluminum layered double hydroxide-folic acid coupling comprises: A1, under a nitrogen-protected anhydrous and oxygen-free environment, dissolving gadolinium nitrate hexahydrate, zinc nitrate hexahydrate, and aluminum nitrate trihydrate in deionized water that has been boiled to remove oxygen, to obtain salt solution A; dissolving sodium hydroxide and sodium carbonate in deionized water, to obtain alkaline solution B; under stirring and a pH of 9.9-10.1, adding salt solution A and alkaline solution B dropwise to a three-necked flask containing deionized water to obtain a reaction mixture; aging the reaction mixture at 64-66°C to obtain a slurry; centrifuging the slurry to obtain a precipitate; and exchanging the precipitate with deionized water and ethanol. The precipitate was washed and dried in a vacuum drying oven at 58-62℃ to obtain the precursor. A2. The precursor was dispersed in a Tris-HCl buffer solution containing sodium dihydrogen phosphate at pH 8.4-8.6 and subjected to ion exchange reaction at 38-42℃. After centrifugation and washing, the intermediate was obtained. The intermediate was ultrasonically dispersed in N,N-dimethylformamide, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added sequentially. The mixture was activated at room temperature. Then, folic acid and triethylamine were added, and the mixture was reacted at 25-30℃ under light-protected conditions to obtain the product. The product was washed with N,N-dimethylformamide and ethanol and dried under vacuum at 38-42℃.

[0011] In this invention, the preparation mechanism of the gadolinium-doped zinc-aluminum layered double hydroxide-folic acid conjugate is based on a cascade reaction of controlled coprecipitation, ion exchange, and surface covalent coupling. First, under a strictly controlled alkaline environment, zinc and aluminum ions hydrolyze and coprecipitate with pre-doped gadolinium ions, forming a layered double hydroxide crystal structure with hydrotalcite characteristics through electrostatic interactions and hydrogen bond networks. The incorporation of gadolinium ions is crucial in this step. Its ionic radius and coordination characteristics differ from those of zinc and aluminum ions, leading to controlled lattice distortion and the creation of more defect sites on the layers. This not only significantly increases the subsequent drug loading capacity but, more importantly, the doped gadolinium ions themselves become catalytically active centers. Their unfilled electron orbitals enable them to catalyze the decomposition of hydrogen peroxide in the tumor microenvironment during subsequent treatment, generating highly cytotoxic hydroxyl radicals, thus endowing the material with inherent chemical kinetic therapeutic potential. The initial product formed is an intermediate for carbonate intercalation. Subsequently, phosphate ion exchange occurs, serving as a crucial bridge connecting subsequent functions. In a weakly alkaline buffer environment, hydrogen phosphate ions, with their stronger interlayer affinity and more suitable charge density, gradually replace carbonate ions in the interlayer, forming a phosphate intercalation structure. This replacement process not only stabilizes the lamination structure but, more importantly, introduces a large number of negatively charged phosphate groups onto the surface of the inorganic lamination, providing chemical reaction anchors for subsequent connections with biomolecules. Finally, covalent coupling of folic acid targeting ligands is achieved through a carbodiimide-mediated amidation reaction. Under the action of the coupling agent, the phosphate groups on the surface of the phosphate intercalation material are activated and undergo efficient condensation with the primary amino groups on the folic acid molecule, forming a stable amide bond that firmly anchors the folic acid molecule to the surface of the inorganic nanocarrier. This amide bond design combines connection stability and intelligent responsiveness; it remains stable in normal physiological environments but can undergo specific cleavage in the weakly acidic microenvironment unique to tumor tissues, thereby achieving acid-base responsive and precise release of the loaded drug. The entire preparation process achieves a seamless integration from inorganic crystal structure modulation and ion exchange engineering to biomolecule functionalization.

[0012] According to a preferred embodiment of the present invention, in step A1, the reaction mixture is crystallized and aged at 64-66°C for 18-20 hours.

[0013] According to a preferred embodiment of the present invention, in step A2, the reaction time at 25-30°C under light-protected conditions is 12-18 hours.

[0014] According to a preferred embodiment of the present invention, the preparation method of the bismuth-tellurium alloy nanoclusters-hyaluronic acid composite includes: B1, dissolving bismuth nitrate pentahydrate and tellurium dioxide in an ethylene glycol solution containing nitric acid and ascorbic acid to obtain solution C; dissolving polyvinylpyrrolidone in ethylene glycol to form solution D; injecting solution C into solution D preheated to 155-165°C under stirring to obtain a mixture; continuously stirring the mixture in an oil bath at 155-165°C to obtain a reaction solution; naturally cooling the reaction solution to room temperature, adding acetone, centrifuging to collect the precipitate, washing the precipitate alternately with ethanol and cyclohexane to obtain PVP-coated BiTe alloy nanoclusters; and then coating the PVP... BiTe alloy nanoclusters were redispersed in anhydrous ethanol, mercaptopropionic acid was added, and the mixture was stirred at 40-50℃. After centrifugation and washing, surface-modified BiTe nanoclusters were obtained. The surface-modified BiTe nanoclusters were then dispersed in anhydrous ethanol to obtain an activated BiTe ethanol dispersion. B2. Mercapto-hyaluronic acid was dissolved in phosphate buffer solution at pH 7.2-7.6 to obtain a mercapto-hyaluronic acid mixture. The activated BiTe ethanol dispersion was added dropwise to the mercapto-hyaluronic acid mixture under ultrasonic conditions. After the addition was complete, ultrasonic treatment was continued to obtain a mixture. The mixture was transferred to a dialysis bag and dialyzed in deionized water. The liquid in the dialysis bag was freeze-dried.

[0015] In this invention, the synthesis mechanism of the bismuth-tellurium alloy nanoclusters-hyaluronic acid composite encompasses three core processes: high-temperature reduction alloying, ligand exchange, and biopolymer interface assembly. The first step is the in-situ synthesis of bismuth-tellurium alloy nanoclusters, based on a synergistic reduction and nucleation growth mechanism within a polyol system. In a high-temperature ethylene glycol solvent, ascorbic acid acts as a strong reducing agent, reducing bismuth and tellurium ions to their zero-valence states; ethylene glycol itself also participates in the reduction and acts as a morphology-directing agent. Due to the tendency of bismuth and tellurium atoms to fuse at high temperatures, the reduced atoms do not nucleate individually, but rather rapidly form alloy nuclei through a co-reduction mechanism. Under the dynamic encapsulation constraint of the surfactant, the nuclei grow into uniformly sized ultra-small nanoclusters. This bismuth-tellurium alloy structure is the core of its functional integration: the high atomic number characteristics of bismuth and tellurium endow it with excellent X-ray blocking ability, making it a highly efficient radiosensitizer; simultaneously, alloying alters the band structure of the single element, enabling it to exhibit significant photothermal conversion performance in the near-infrared II window, which can be used for photoacoustic imaging and photothermal therapy. The second step involves ligand engineering on the surface of the alloy nanoclusters. While the initial coating of long polymer chains stabilizes the nanoclusters, it also severely shields their surface activity. By introducing small-molecule mercaptopropionic acid for ligand exchange, the terminal thiol groups form stronger sulfur-tellurium bonds with tellurium atoms on the nanocluster surface, partially replacing the original polymer chains and exposing the carboxyl functional groups on the nanocluster surface. This step is crucial, as it preserves the dispersion stability of the nanoclusters while providing an active interface for further reaction with biomolecules. The third step is the composite assembly of hyaluronic acid. Thiol-based hyaluronic acid chains dissolved in buffer solution interact with the surface of carboxyl-modified nanoclusters via their terminal thiol groups. This interaction may involve secondary chemical bonding between carboxyl and thiol groups, or it may form a more robust connection under the action of a cross-linking agent. Ultimately, the long-chain hyaluronic acid molecules act as "anchors," connecting and encapsulating multiple nanoclusters to form a complex. In this structure, hyaluronic acid not only acts as a targeting ligand to recognize CD receptors on the surface of tumor cells, but the disulfide bonds between its chains also endow it with reduction responsiveness. When the complex enters the glutathione-rich intracellular environment of tumor cells, the disulfide bonds break, causing the hyaluronic acid shell to dissociate, thereby exposing the internal alloy nanoclusters and activating their radiosensitization and photothermal functions, realizing a smart switch for therapeutic function.

[0016] According to a preferred embodiment of the present invention, in step B1, the mixture is continuously stirred and reacted in an oil bath at 155-165°C for 3-5 hours.

[0017] According to a preferred embodiment of the present invention, in step B2, the duration of continued ultrasonic treatment is 30-40 minutes.

[0018] In a second aspect, the present invention provides a bladder cancer targeted nanomedicine prepared according to the method for preparing the bladder cancer targeted nanomedicine described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves precise regulation of the physicochemical properties and targeting function of nanomedicines by constructing a hybrid structure with gemcitabine-loaded polylactic-co-glycolic acid copolymer nanoparticles as the core and two functionalized inorganic compounds co-assembled on the surface. The introduced cationic lipids make the surface of the core nanoparticles positively charged, which not only significantly improves the electrostatic binding force between them and the two negatively charged functional compounds, ensuring that the hybrid shell is firmly assembled and uniformly coated, thereby improving the overall stability of the nano-formulation; more importantly, this design makes the final nanomedicine have suitable size and surface characteristics, which is conducive to prolonging the mucosal retention time after bladder instillation and promoting the penetration of tumor tissue. More critically, the two groups assembled on the surface are coupled with folic acid and hyaluronic acid, respectively, which endow the nanomedicine with dual active targeting capabilities. It can simultaneously recognize the folic acid receptor and CD44 receptor overexpressed on the surface of bladder cancer cells, achieving highly selective recognition and binding to tumor cells, improving the drug accumulation efficiency from the source, and significantly reducing non-specific damage to normal urothelial cells, laying a material basis for reducing the toxic side effects of chemotherapy.

[0020] (2) The two inorganic functional compounds that are unique in this invention are not simple carriers, but intelligent units that integrate diagnostic, targeted, responsive drug release and synergistic therapeutic functions. The structure of the gadolinium-doped zinc-aluminum layered double hydroxide folic acid conjugate achieves the integration of multiple functions: the doping of gadolinium ions not only endows the material with excellent magnetic resonance imaging contrast capabilities, which facilitates real-time monitoring and efficacy evaluation of the treatment process, but also allows it to catalyze hydrogen peroxide to generate highly toxic hydroxyl radicals in the tumor microenvironment, exerting an intrinsic chemokinetic therapeutic effect; at the same time, the chemical bond connecting folic acid can be specifically broken in the weakly acidic environment of tumor tissue, realizing the pH-responsive and precise release of chemotherapy drugs. On the other hand, the bismuth-tellurium alloy nanocluster hyaluronic acid complex also possesses multifunctionality: the high atomic number bismuth-tellurium alloy exhibits excellent X-ray attenuation capabilities and near-infrared II photothermal conversion performance, making it a highly efficient radiosensitizer and photoacoustic imaging probe; while the hyaluronic acid chains, bound to the alloy nanoclusters through dynamic covalent bonds, can actively target the CD44 receptor and dissociate under the influence of high concentrations of glutathione within tumor cells, achieving reduction-responsive drug release and sensitizer exposure. The synergistic effect of these two compounds enables the nanomedicine, upon reaching the tumor site, to respond to microenvironmental signals and achieve intelligent, cascaded release of drugs and therapeutic factors.

[0021] (3) All the above-mentioned technical features work together to achieve excellent therapeutic effects. The nanomedicine system constructed in this invention successfully integrates multiple modes such as chemotherapy, chemokinetic therapy, radiosensitization, and even photothermal therapy. Dual targeting ensures efficient delivery of the therapeutic weapon, dual response release ensures that the therapeutic activity is activated at the right time and place, and the synergistic effect of multiple mechanisms can launch a multi-pathway and multi-level joint attack on tumor cells, effectively overcoming the single-drug resistance of tumor cells and significantly enhancing the killing effect on bladder tumor cells. In summary, this invention not only provides a novel method for preparing nanomedicines, but also creates a highly efficient platform integrating targeting, imaging, intelligent drug release, and synergistic therapy, which is expected to significantly improve the treatment effect of bladder cancer, improve patient prognosis, and has important clinical application value and translational prospects. Detailed Implementation

[0022] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0023] Example 1

[0024] This embodiment provides a method for preparing bladder cancer-targeting nanomedicines, and the specific implementation steps are as follows: Preparation of gadolinium-doped zinc-aluminum layered double hydroxide-folic acid conjugate Precursor synthesis: In an inert atmosphere glove box continuously purged with high-purity nitrogen, weigh 0.10 g of gadolinium nitrate hexahydrate, 2.00 g of zinc nitrate hexahydrate, and 0.90 g of aluminum nitrate trihydrate. Dissolve the above salts together in 100 mL of deionized water that has been boiled and deoxygenated by purging with nitrogen for 30 minutes, and stir magnetically until completely clear to obtain salt solution A. Separately weigh 1.50 g of sodium hydroxide and 1.00 g of sodium carbonate, and dissolve them in 100 mL of deionized water to obtain alkaline solution B. Add 50 mL of deionized water to a 500 mL three-necked flask, and install a mechanical stirrer, pH electrode, and two constant flow titration pumps. Place the flask in a 65 °C water bath and start stirring. Simultaneously add salt solution A and alkaline solution B dropwise to the three-necked flask at a rate of 1 mL / min using the titration pumps. During this process, add 0.5 mol / L NaOH solution dropwise using an automatic titrator to precisely stabilize the pH of the reaction system at 10.0 ± 0.1. The dropwise addition process lasted for 2 hours. After the addition was complete, the reaction mixture was kept in a 65°C water bath with continuous stirring for 18 hours to allow it to crystallize and age. After the reaction was complete, the resulting white slurry was transferred to a centrifuge tube and centrifuged at 10,000 rpm for 10 minutes to collect the precipitate. The precipitate was washed three times each with deionized water and anhydrous ethanol, alternating between the two. The washed precipitate was placed in a vacuum drying oven and dried at 60°C for 12 hours. After grinding, a white powdery precursor, Gd-ZnAl-CO3LDH, was obtained.

[0025] Phosphate intercalation: Weigh 1.00 g of the dried precursor and disperse it in 50 mL of 0.40 mol / L sodium dihydrogen phosphate Tris-HCl buffer solution (pH 8.5). Place the suspension in a 40°C water bath shaker and react at 150 rpm for 24 hours. After the reaction is complete, centrifuge to collect the precipitate, wash it three times with deionized water to obtain the phosphate intercalation intermediate Gd-ZnAl-PO4LDH.

[0026] Folic acid coupling: Weigh 0.50 g of the above intermediate and place it in a 100 mL round-bottom flask. Add 50 mL of anhydrous N,N-dimethylformamide and sonicate for 30 minutes. Then, add 0.20 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.12 g of N-hydroxysuccinimide sequentially, and activate the carboxyl groups by magnetic stirring at room temperature for 30 minutes. Subsequently, add 0.30 g of folic acid and 100 μL of triethylamine. Wrap the flask with aluminum foil to protect it from light and place it in an oil bath at 28 °C. Stir magnetically for 15 hours. After the reaction, centrifuge the mixture. Wash the precipitate three times each with N,N-dimethylformamide and anhydrous ethanol to thoroughly remove unreacted reagents and byproducts. Place the final product in a vacuum drying oven and dry at 40 °C for 8 hours to obtain the gadolinium-doped zinc-aluminum layered double hydroxide-folic acid coupling compound.

[0027] Preparation of bismuth-tellurium alloy nanoclusters-hyaluronic acid complex

[0028] Synthesis of BiTe alloy nanoclusters: 0.485 g of bismuth nitrate pentahydrate and 0.160 g of tellurium dioxide were weighed and dissolved together in 20 mL of ethylene glycol solution containing 0.10 mol / L nitric acid and 0.20 mol / L ascorbic acid. The solution was magnetically stirred until a clear solution C was formed. In another 100 mL three-necked flask, 0.800 g of polyvinylpyrrolidone was weighed and dissolved in 30 mL of ethylene glycol to form solution D. Solution D was heated to 160 °C and kept at this temperature. Under magnetic stirring, solution C was rapidly injected into solution D over 1 minute using a syringe pump. The reaction mixture immediately turned dark brown. The oil bath temperature was maintained at 160 °C, and the reaction was continuously stirred for 3 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. An equal volume of acetone was added to the reaction solution, and the black precipitate was collected by centrifugation at 12000 rpm for 15 minutes. The precipitate was washed three times each with anhydrous ethanol and cyclohexane, alternating between the two. The washed precipitate was redispersed in 20 mL of anhydrous ethanol to obtain an ethanol dispersion of BiTe-PVP nanoclusters.

[0029] Ligand exchange: Take the above BiTe-PVP ethanol dispersion (containing approximately 0.20 g of nanoclusters) and add 0.10 g of mercaptopropionic acid. Place the mixture in an oil bath at 45°C and stir magnetically for 5 hours. After the reaction is complete, collect the precipitate by centrifugation at 12000 rpm for 10 minutes, and wash twice with anhydrous ethanol to obtain BiTe nanoclusters with mercaptopropionic acid modified on the surface.

[0030] Hyaluronic acid composite: Surface-modified BiTe nanoclusters (approximately 0.15 g) were redispersed in 10 mL of anhydrous ethanol to obtain an "activated BiTe ethanol dispersion". Separately, 0.20 g of thiol-hyaluronic acid was dissolved in 10 mL of pH 7.4 phosphate buffer to obtain a thiol-hyaluronic acid mixture. With the assistance of an ice-water bath and an ultrasonic cell disruptor (200 W, 2 seconds operation, 3-second interval), the activated BiTe ethanol dispersion was added dropwise to the thiol-hyaluronic acid mixture. After the addition was complete, sonication was continued for 30 minutes. The mixture was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in 4 L of deionized water for 48 hours, with the dialysate changed every 8 hours. After dialysis, the liquid in the dialysis bag was freeze-dried to obtain a grayish-black sponge-like solid, which is the bismuth-tellurium alloy nanocluster-hyaluronic acid composite.

[0031] Preparation of bladder cancer targeted nanomedicines

[0032] Preparation of drug-loaded PLGA nanoparticles: 0.10 g of gemcitabine was weighed and dissolved in 1 mL of deionized water containing 0.01 g of poloxamer 188. The mixture was vortexed and mixed to form the inner aqueous phase (W1). 0.50 g of polylactic acid-glycolic acid copolymer, 0.05 g of 1,2-distearate-sn-glycerol-3-phosphate ethanolamine-N-[methoxy(polyethylene glycol)-2000], and 0.03 g of 1,2-dioleoyl-3-trimethylammonium-propane were weighed and dissolved together in 2 mL of dichloromethane. The mixture was vortexed until completely dissolved to form the oil phase (O). Phase W1 was injected into phase O under ice-water bath conditions. Immediately afterward, the mixture was sonicated in the ice-water bath at 100 W power (3 seconds on, 2 seconds off) for a total of 2 minutes to form a pre-emulsion (W1 / O). This pre-emulsion was then quickly poured into 10 mL of the outer aqueous phase (W2) containing 0.20 g of polyvinyl alcohol. The emulsion was homogenized and emulsified at 10,000 rpm for 3 minutes using a high-speed homogenizer to form a double emulsion (W1 / O / W2). The double emulsion was transferred to a 250 mL open beaker and magnetically stirred at room temperature for 4 hours to allow complete evaporation of dichloromethane and solidification of the nanoparticles. The solidified nanoparticle suspension was centrifuged at 20,000 rpm for 30 minutes at 4 °C, and the precipitate was collected. The precipitate was resuspended in deionized water and washed three times by centrifugation to obtain gemcitabine-loaded PLGA nanoparticles.

[0033] Surface functionalization assembly: The washed drug-loaded PLGA nanoparticles were redispersed in 5 mL of Tris-HCl buffer (pH 8.0, 10 mmol / L). 0.05 g of the gadolinium-doped zinc-aluminum layered double hydroxide-folic acid conjugate prepared in step one and 0.05 g of the bismuth-tellurium alloy nanoclusters-hyaluronic acid complex prepared in step two were weighed and added to the nanoparticle dispersion. The mixture was placed on a horizontal shaker and incubated at 150 rpm for 13 hours at room temperature. After incubation, the mixture was centrifuged at 15000 rpm for 20 minutes at 4°C to collect the product. The product was washed twice with deionized water. Finally, the product was redispersed in 5 mL of sterile phosphate buffer (pH 7.4) to obtain the final bladder cancer-targeting nanomedicine of this invention.

[0034] Example 2

[0035] The difference between this embodiment and Example 1 is that a gadolinium-doped zinc-aluminum layered double hydroxide-folic acid conjugate is prepared.

[0036] Under nitrogen protection, 0.15 g of gadolinium nitrate hexahydrate, 1.80 g of zinc nitrate hexahydrate, and 0.85 g of aluminum nitrate trihydrate were dissolved in 100 mL of deoxygenated deionized water to obtain a salt solution. 1.20 g of sodium hydroxide and 0.80 g of sodium carbonate were dissolved in 100 mL of deionized water to obtain an alkaline solution. Under conditions of a 64°C water bath and pH 10.05, both solutions were simultaneously added dropwise to 50 mL of water. After the addition was complete, the solution was allowed to crystallize and age for 20 hours. After centrifugation and washing, the solution was dried at 60°C to obtain the precursor. 1.20 g of this precursor was dispersed in 50 mL of 0.35 mol / L sodium dihydrogen phosphate Tris-HCl buffer at pH 8.4. The solution was shaken and exchanged at 40°C for 22 hours, followed by centrifugation and washing to obtain the intermediate. 0.60 g of the intermediate was dispersed in 50 mL of DMF, and 0.25 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.15 g of N-hydroxysuccinimide were added. The mixture was activated at room temperature for 30 minutes. 0.25 g of folic acid and 80 μL of triethylamine were then added, and the mixture was reacted at 26 °C for 18 hours in the dark. After the reaction, the product was centrifuged, washed successively with DMF and ethanol, and dried under vacuum at 40 °C to obtain a pale yellow powder.

[0037] Preparation of bismuth-tellurium alloy nanoclusters-hyaluronic acid complex

[0038] Solution C was prepared by dissolving 0.500 g of bismuth nitrate pentahydrate and 0.150 g of tellurium dioxide in 20 mL of ethylene glycol containing 0.12 mol / L nitric acid and 0.15 mol / L ascorbic acid. Solution D was prepared by dissolving 0.750 g of polyvinylpyrrolidone in 30 mL of ethylene glycol. Solution D, preheated to 158 °C, was rapidly poured into solution C with stirring, and the reaction was carried out in a 158 °C oil bath with continuous stirring for 3.5 hours. After cooling, an equal volume of acetone was added, and the precipitate was collected by centrifugation at 12000 rpm for 15 minutes. The precipitate was washed three times alternately with ethanol and cyclohexane. 0.18 g of the obtained nanoclusters were redispersed in 20 mL of anhydrous ethanol, and 0.08 g of mercaptopropionic acid was added. The reaction was carried out by stirring at 42 °C for 4.5 hours. After centrifugation and washing, surface-modified BiTe nanoclusters were obtained. 0.12 g of the nanoclusters were dispersed in 10 mL of anhydrous ethanol to obtain an activated dispersion. Separately, 0.15 g of thiol-hyaluronic acid was dissolved in 10 mL of phosphate buffer (pH 7.3). The activated dispersion was added dropwise to the hyaluronic acid solution under sonication in an ice bath, and sonication was continued for 30 minutes after the addition was complete. The mixture was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in 4 L of deionized water for 44 hours, with the water changed 5 times during the process. Finally, the solution was freeze-dried to obtain a gray-black solid.

[0039] Preparation of bladder cancer targeted nanomedicines

[0040] 0.15 g of gemcitabine was dissolved in 1 mL of deionized water containing 0.015 g of poloxamer 188 to obtain the inner aqueous phase. 0.60 g of polylactic acid-glycolic acid copolymer, 0.08 g of 1,2-distearate-sn-glycerol-3-phosphate ethanolamine-N-[methoxy(polyethylene glycol)-2000], and 0.05 g of 1,2-dioleoyl-3-trimethylammonium-propane were dissolved in 1.5 mL of dichloromethane to obtain the oil phase. The inner aqueous phase was injected into the oil phase under ice-water bath conditions, and the mixture was ultrasonically emulsified at 100 W for 2 minutes to obtain the primary emulsion. This primary emulsion was poured into 10 mL of an aqueous solution containing 0.25 g of polyvinyl alcohol and homogenized at 9500 rpm for 2.5 minutes to obtain the secondary emulsion. The secondary emulsion was stirred at room temperature for 4 hours to evaporate the solvent. The suspension was centrifuged at 20000 rpm for 30 minutes at 4 °C and washed three times with water to obtain drug-loaded nanoparticles. The nanoparticles were dispersed in 5 mL of pH 8.0 Tris-HCl buffer, and 0.07 g of the aforementioned modified LDH and 0.03 g of the modified BiTe complex were added. The mixture was incubated at room temperature with shaking for 12 hours. The product was collected by centrifugation, washed twice with water, and then dispersed in 5 mL of pH 7.4 phosphate buffer.

[0041] Example 3

[0042] The difference between this embodiment and Example 1 is that a gadolinium-doped zinc-aluminum layered double hydroxide-folic acid conjugate is prepared.

[0043] Under nitrogen protection, 0.08 g of gadolinium nitrate hexahydrate, 2.10 g of zinc nitrate hexahydrate, and 0.95 g of aluminum nitrate trihydrate were dissolved in 100 mL of deoxygenated deionized water to obtain a salt solution. 1.60 g of sodium hydroxide and 1.10 g of sodium carbonate were dissolved in 100 mL of deionized water to obtain an alkaline solution. Under conditions of a 66°C water bath and pH 9.95, both solutions were simultaneously added dropwise to 50 mL of water. After the addition was complete, the solution was allowed to crystallize and age for 19 hours. After centrifugation and washing, the solution was dried at 60°C to obtain the precursor. 0.80 g of this precursor was dispersed in 50 mL of 0.45 mol / L sodium dihydrogen phosphate Tris-HCl buffer at pH 8.6, and the solution was shaken and exchanged at 39°C for 26 hours. After centrifugation and washing, the intermediate was obtained. 0.40 g of the intermediate was dispersed in 50 mL of DMF, and 0.15 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.10 g of N-hydroxysuccinimide were added. The mixture was activated at room temperature for 30 minutes. 0.35 g of folic acid and 120 μL of triethylamine were then added, and the mixture was reacted at 30 °C for 12 hours in the dark. After the reaction, the product was centrifuged, washed successively with DMF and ethanol, and dried under vacuum at 40 °C to obtain a pale yellow powder.

[0044] Preparation of bismuth-tellurium alloy nanoclusters-hyaluronic acid complex

[0045] Solution C was prepared by dissolving 0.470 g of bismuth nitrate pentahydrate and 0.170 g of tellurium dioxide in 20 mL of ethylene glycol containing 0.08 mol / L nitric acid and 0.25 mol / L ascorbic acid. Solution D was prepared by dissolving 0.850 g of polyvinylpyrrolidone in 30 mL of ethylene glycol. Solution D, preheated to 162 °C, was rapidly added to solution C with stirring, and the reaction was carried out with continuous stirring in an oil bath at 162 °C for 4.5 hours. After cooling, an equal volume of acetone was added, and the precipitate was collected by centrifugation at 12000 rpm for 15 minutes. The precipitate was washed three times alternately with ethanol and cyclohexane. 0.22 g of the obtained nanoclusters were redispersed in 20 mL of anhydrous ethanol, and 0.12 g of mercaptopropionic acid was added. The reaction was carried out with stirring at 48 °C for 5.5 hours. After centrifugation and washing, surface-modified BiTe nanoclusters were obtained. 0.18 g of these nanoclusters were dispersed in 10 mL of anhydrous ethanol to obtain an activated dispersion. Separately, 0.25 g of thiol-hyaluronic acid was dissolved in 10 mL of phosphate buffer (pH 7.5). The activated dispersion was added dropwise to the hyaluronic acid solution under sonication in an ice bath, and sonication was continued for 30 minutes after the addition was complete. The mixture was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in 4 L of deionized water for 52 hours, with the water changed 6 times during the process. Finally, the solution was freeze-dried to obtain a gray-black solid.

[0046] Preparation of bladder cancer targeted nanomedicines

[0047] 0.05 g of gemcitabine was dissolved in 1 mL of deionized water containing 0.008 g of poloxamer 188 to obtain the inner aqueous phase. 0.45 g of polylactic acid-glycolic acid copolymer, 0.03 g of 1,2-distearate-sn-glycerol-3-phosphate ethanolamine-N-[methoxy(polyethylene glycol)-2000], and 0.01 g of 1,2-dioleoyl-3-trimethylammonium-propane were dissolved in 2.5 mL of dichloromethane to obtain the oil phase. The inner aqueous phase was injected into the oil phase under ice-water bath conditions, and the mixture was ultrasonically emulsified at 100 W for 2 minutes to obtain the primary emulsion. This primary emulsion was poured into 10 mL of an aqueous solution containing 0.15 g of polyvinyl alcohol and homogenized at 10500 rpm for 3.5 minutes to obtain the secondary emulsion. The secondary emulsion was stirred at room temperature for 4 hours to evaporate the solvent. The suspension was centrifuged at 20000 rpm for 30 minutes at 3°C ​​and washed three times with water to obtain drug-loaded nanoparticles. The nanoparticles were dispersed in 5 mL of pH 8.0 Tris-HCl buffer, and 0.03 g of the aforementioned modified LDH and 0.08 g of the modified BiTe complex were added. The mixture was incubated at room temperature with shaking for 14 hours. The product was collected by centrifugation, washed twice with water, and then dispersed in 5 mL of pH 7.4 phosphate buffer.

[0048] Comparative Example 1

[0049] The difference between this comparative example and Example 1 is that 1,2-dioleoyl-3-trimethylammonium-propane was not added during the preparation of the oil phase. Specifically, 0.10 g of gemcitabine was weighed and dissolved in 1 mL of deionized water containing 0.01 g of poloxamer 188. 0.50 g of polylactic acid-glycolic acid copolymer and 0.05 g of 1,2-distearate-sn-glycerol-3-phosphate ethanolamine-N-[methoxy(polyethylene glycol)-2000] were weighed and dissolved in 2 mL of dichloromethane. The subsequent preparation of the primary emulsion, secondary emulsion, nanoparticle solidification, and washing steps were exactly the same as in Example 1. After dispersing the obtained drug-loaded PLGA nanoparticles in 5 mL of Tris-HCl buffer, 0.05 g of gadolinium-doped zinc-aluminum layered double hydroxide-folic acid coupling compound and 0.05 g of bismuth-tellurium alloy nanoclusters-hyaluronic acid complex, the same amount as in Example 1, were added. The mixture was then shaken, incubated, centrifuged, washed, and dispersed in the same manner to obtain comparative nanodrug 1.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 1 is that, in step S2, instead of adding gadolinium-doped zinc-aluminum layered double hydroxide-folic acid coupling compound, an equal mass of undoped and uncoupled ordinary zinc-aluminum layered double hydroxide is added. This ordinary LDH is prepared using only the method in step A1 of Example 1 (without using gadolinium nitrate), yielding ZnAl-C. LDH was used, and the same phosphate intercalation treatment was performed, but without folic acid coupling. In the preparation of bladder cancer-targeting nanomedicines, 0.05g of this ordinary ZnAl-P... Except for LDH substitution for modified LDH, all other raw materials, dosages, and steps were kept completely consistent with those in Example 1, resulting in comparative nanomedicine 2.

[0052] Comparative Example 3

[0053] The difference between this comparative example and Example 1 is that, in step S2, the bismuth-tellurium alloy nanoclusters-hyaluronic acid complex is not added; instead, an equal mass of unrecombined ordinary hyaluronic acid is added. In the preparation of the bladder cancer-targeting nanomedicine, except for replacing the modified BiTe complex with 0.05g of ordinary hyaluronic acid (molecular weight approximately 10kDa), all other raw materials, amounts, and steps are completely consistent with Example 1, resulting in comparative nanomedicine 3.

[0054] In accordance with national and industry standard testing specifications, all performance tests were conducted under the same environmental conditions, using bladder cancer-targeting nanomedicines prepared in Examples 1-3 and comparative nanomedicines prepared in Comparative Examples 1-3. First, the hydrated particle size distribution and Zeta potential of each sample were determined using dynamic light scattering at 25°C. After appropriate dilution with deionized water, the samples were placed in a standard sample cell. Under conditions of a laser wavelength of 633 nm and a scattering angle of 90°, each sample was measured three times consecutively in parallel. The instrument software automatically calculated and provided the average value and standard deviation of the particle size polydispersity index and Zeta potential.

[0055] Next, high-performance liquid chromatography (HPLC) was used to determine the encapsulation efficiency and drug loading. The specific steps are as follows: 200 μL of freshly prepared nanoparticle suspension was accurately measured, 800 μL of acetonitrile was added, and the mixture was vortexed to break the emulsion. The volume was then adjusted to an appropriate level, filtered through a 0.22 μm microporous membrane, and used as the test solution. The total drug content was determined by HPLC under the conditions of a C18 column, a methanol-phosphate buffer mobile phase, a detection wavelength of 268 nm, and a flow rate of 1.0 mL / min. Simultaneously, an equal volume of the same batch of nanoparticle suspension was taken, centrifuged at 20,000 rpm for 30 minutes at 4 °C, and the supernatant was carefully collected. The free drug content was determined under the same HPLC conditions. The encapsulation efficiency and drug loading were calculated using the following formulas: Encapsulation efficiency = (total drug content - free drug content) / total drug content × 100%, Drug loading = (total drug content - free drug content) / total mass of nanoparticles × 100%.

[0056] In vitro drug release behavior studies were conducted using the dialysis method: Nanoparticles containing 1.0 mg of gemcitabine were accurately weighed and placed in pretreated dialysis bags with a molecular weight cutoff of 3500 Da. The bags were then immersed in 50 mL of pH 7.4 phosphate buffer release medium and pH 5.5 phosphate buffer release medium containing 10 mM glutathione, respectively. The entire system was placed in a 37°C constant-temperature shaking water bath and shaken at 100 rpm. At predetermined time points (e.g., 1, 2, 4, 8, 12, 24, 48 hours), all release media were collected, and an equal volume of fresh medium at the same temperature was immediately added to maintain the trough conditions. The collected release media samples were filtered through a 0.22 μm filter membrane, and the gemcitabine concentration was determined using the aforementioned HPLC conditions. The cumulative release percentage of the drug at each time point was calculated, with particular emphasis on recording the release data over 24 hours.

[0057] In vitro cytotoxicity was evaluated using the MTT assay: T24 human bladder cancer cell line was used as a model cell line, and cells were cultured at 5 × 10⁶ cells per well. 3 Cells were seeded at a density of 1000 μg / mL in 96-well plates and incubated at 37°C with 5% CO2 for 24 hours to allow cell adhesion. Then, free gemcitabine solution, samples from each example, and comparative sample at a series of concentration gradients (e.g., 0.01, 0.1, 1, 10 μg / mL) were added, with six replicates for each concentration. A blank control group containing only culture medium was also included. After incubation for another 48 hours, 20 μL of LTT solution (5 mg / mL) was added to each well, and incubation continued for another 4 hours. The culture medium in each well was carefully aspirated, and 150 μL of dimethyl sulfoxide was added to each well. The plates were then shaken slowly on a plate shaker for 10 minutes to fully dissolve the gemcitabine crystals. Finally, the absorbance of each well was measured at 490 nm using a microplate reader, cell viability was calculated, and the dose-response curve was fitted using nonlinear regression to determine the concentration required to inhibit 50% cell growth, i.e., the half-maximal inhibitory concentration (MCC).

[0058] Cell uptake assessment was performed using flow cytometry: Well-grown T24 cells were seeded at a density of 1 × 10⁵ cells per well in 12-well plates and cultured for 24 hours. Nanomedicines were labeled with the near-infrared fluorescent dye DiR according to standard procedures to prepare fluorescently labeled nanomedicines. After washing the cells twice with pre-warmed culture medium, 1 mL of fresh culture medium containing each labeled nanomedicine with the same DiR fluorescence intensity was added to each well, and incubation continued for 2 hours. After incubation, the cells were washed three times with pre-cooled phosphate-buffered saline (PBSS) to terminate uptake and remove unabsorbed nanomedicines. The cells were then digested with trypsin and collected, resuspended in PBSS containing 1% fetal bovine serum. Immediately, flow cytometry was used for detection. The excitation wavelength was set to 633 nm, and fluorescence signals above 660 nm were collected. At least 10,000 cells were analyzed per experiment, and the instrument software output the average fluorescence intensity of the cell population for quantitative comparison.

[0059] In vivo targeting and efficacy assessment were conducted by establishing an orthotopic bladder cancer model in nude mice: Under aseptic conditions, T24 cells stably expressing luciferase (5 × 10^5 cells / 20 μL) were slowly injected into the bladder wall of female BALB / cnude mice via catheter to establish the model; after tumor growth for about one week, tumor formation was confirmed by monitoring bioluminescence signals using a small animal in vivo imaging system. Tumor-bearing mice were randomly divided into a model control group, a free gemcitabine group, Example 1 group, Comparative Example 1 group, Comparative Example 2 group, and Comparative Example 3 group, with at least 5 mice in each group; gemcitabine was administered at a dose of 5 mg / kg via tail vein injection or bladder instillation, once every three days for a total of five times; in the first... At specific time points after the first dose (e.g., 2, 6, 12, 24 hours), the distribution of fluorescently labeled nanomedicines in vivo was imaged using a small animal in vivo imaging system. The tumor targeting index was calculated by analyzing the fluorescence signal intensity of the tumor region and the contralateral normal tissue region. During the treatment period, the longest and shortest diameters of the tumor were measured twice a week using precision calipers, and the tumor volume was calculated according to the formula. The weight of the mice was also recorded to monitor safety. After the treatment, the mice were sacrificed, the tumors were removed and weighed, and the tumor inhibition rate of each treatment group was calculated. At the same time, major organs such as the heart, liver, spleen, lungs, and kidneys were taken for hematoxylin-eosin staining, and histopathological changes were observed under an optical microscope to assess the potential systemic toxicity of the drug.

[0060] The performance test data above are shown in Table 1.

[0061] Table 1 Performance Test Results

[0062] The test results in Table 1 above clearly show that Examples 1-3 systematically solve the key technical problems commonly found in existing nanomedicine therapy for bladder cancer, such as low targeting efficiency, uncontrollable drug release, easy drug resistance to monotherapy, and separation of diagnosis and treatment, compared to Comparative Examples 1-3.

[0063] Specifically, in terms of targeting efficiency and cellular uptake, the sample in this example, with its moderate positive charge (Zeta potential +12.7 to +17.6 mV) and dual targeting ligands (folic acid and hyaluronic acid), achieved an average fluorescence intensity of 8700-9250 during cellular uptake and an in vivo tumor targeting index of 7.2-8.5. This is a significant improvement compared to Comparative Example 1 (uptake intensity 3100, targeting index 2.1), which has a strongly negative charge and lacks active targeting ability, and Comparative Examples 2 and 3 (uptake intensity 5200 and 4800, targeting index 4.3 and 3.8), which respectively lack folic acid or hyaluronic acid targeting. This demonstrates that the present invention effectively solves the problem of insufficient tumor accumulation caused by non-specific adsorption and a single targeting strategy of traditional nanoparticles through the introduction of cationic lipids and dual ligand modification.

[0064] Secondly, regarding the intelligent control of drug release, the example demonstrated an excellent dual-response characteristic, with a 24-hour drug release rate of 68.9-75.1% in a simulated tumor microenvironment (pH 5.5 + GSH) and less than 21% in a physiological environment (pH 7.4). In contrast, Comparative Example 2 showed a significantly lower drug release rate of only 45.2% in the same simulated tumor environment, indicating that the lack of a gadolinium-doped LDH pH response mechanism and the acid-sensitive cleavage characteristics of folic acid coupling bonds weaken the drug's responsiveness in acidic environments. The response release rate of Comparative Example 3 (58.4%) was also lower than that of the example, indicating that the lack of a BiTe-HA-based GSH response pathway would affect the drug release efficiency. The burst release of Comparative Example 1 at a physiological pH of 35.2% revealed the problem of unstable functional shell assembly and easy drug leakage due to the lack of surface positive charge. The example successfully solved this controlled release problem by assembling a stable electrostatic shell.

[0065] Furthermore, in terms of synergistic therapeutic efficacy and overcoming drug resistance, the example showed the lowest half-maximal inhibitory concentration (IC50) for T24 cells, with an IC50 value of 0.32-0.38 μg / mL, exhibiting the strongest cell-killing efficacy and a final tumor inhibition rate of 83.7-89.2% in vivo. In contrast, the efficacy of the three comparative examples decreased sequentially. Comparative example 1 had an inhibition rate of only 45.3% due to the dual deficiency of targeting and controlled release. Comparative examples 2 and 3, due to the lack of chemokinetic therapy / folate targeting and radiosensitization / HA targeting functions, respectively, had inhibition rates of only 62.1% and 58.8%. This clearly demonstrates that the integrated chemotherapy, chemokinetic therapy, and radiosensitization modalities of this invention produce a significant synergistic effect, effectively solving the problem of drug resistance easily generated by single chemotherapy drugs.

[0066] Finally, the gadolinium doping-provided magnetic resonance imaging capability and the bismuth-tellurium alloy-provided radiosensitization and potential photothermal imaging capabilities in the embodiments of this invention enable visualized monitoring and precise intervention during the treatment process, solving the dilemma of separation of diagnosis and treatment and the inability to assess efficacy in real time in traditional therapies. In summary, Examples 1-3, through careful material design and structural assembly, have achieved substantial progress in targeted therapy, controlled release, synergistic therapy, and integrated diagnosis and treatment, comprehensively surpassing the control regimen and successfully addressing the key challenges in the current field of bladder cancer treatment.

Claims

1. A method for preparing a bladder cancer-targeting nanomedicine, characterized in that the steps include... include: S1. By weight, dissolve 5-15 parts of gemcitabine in deionized water containing 0.5-2.0 parts of poloxamer 188 to obtain an aqueous phase; dissolve 40-60 parts of polylactic acid-glycolic acid copolymer, 2-10 parts of 1,2-distearate-sn-glycerol-3-phosphate ethanolamine-N-[methoxy(polyethylene glycol)-2000], and 1-5 parts of 1,2-dioleoyl-3-trimethylammonium-propane in 1-3 mL of dichloromethane to obtain an oil phase; inject the aqueous phase into the oil phase under ice-water bath conditions and sonicate to obtain a primary emulsion; pour the primary emulsion into an aqueous phase containing 100-300 parts of polyvinyl alcohol and emulsify under stirring to obtain a secondary emulsion; S2. Transfer the double emulsion to a beaker and stir at room temperature to obtain a solidified nanoparticle suspension. Centrifuge the solidified nanoparticle suspension at 2-4°C, collect the precipitate, and wash it with deionized water to obtain gemcitabine-loaded PLGA nanoparticles. Redisperse the gemcitabine-loaded PLGA nanoparticles in Tris-HCl buffer, add 2.5-15 parts of gadolinium-doped zinc-aluminum layered double hydroxide-folic acid coupling compound and 2.5-15 parts of bismuth-tellurium alloy nanoclusters-hyaluronic acid complex to obtain a mixture. Incubate the mixture with shaking at room temperature. After incubation, centrifuge to collect the product, wash the product with deionized water to obtain the washed product, and redisperse the washed product in phosphate buffer. The preparation method of the gadolinium-doped zinc-aluminum layered double hydroxide-folic acid coupling compound includes: A1. Under an anhydrous and oxygen-free environment protected by nitrogen, gadolinium nitrate hexahydrate, zinc nitrate hexahydrate, and aluminum nitrate trihydrate are dissolved in deionized water that has been boiled to remove oxygen, to obtain salt solution A; sodium hydroxide and sodium carbonate are dissolved in deionized water, to obtain alkaline solution B; under stirring and at a pH of 9.9-10.1, salt solution A and alkaline solution B are added dropwise to a three-necked flask containing deionized water to obtain a reaction mixture; the reaction mixture is crystallized and aged at 64-66℃ to obtain a slurry; the slurry is centrifuged to obtain a precipitate; the precipitate is washed alternately with deionized water and ethanol. Finally, the precursor was dried in a vacuum drying oven at 58-62℃ to obtain the precursor; A2, the precursor was dispersed in a Tris-HCl buffer solution containing sodium dihydrogen phosphate at pH 8.4-8.6, and subjected to ion exchange reaction at 38-42℃. After centrifugation and washing, the intermediate was obtained; the intermediate was ultrasonically dispersed in N,N-dimethylformamide, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added sequentially, and the mixture was activated at room temperature; then folic acid and triethylamine were added, and the mixture was reacted at 25-30℃ under light-protected conditions to obtain the product; the product was washed with N,N-dimethylformamide and ethanol, and then vacuum dried at 38-42℃. The preparation method of the bismuth-tellurium alloy nanoclusters-hyaluronic acid composite includes: B1, dissolving bismuth nitrate pentahydrate and tellurium dioxide in an ethylene glycol solution containing nitric acid and ascorbic acid to obtain solution C; dissolving polyvinylpyrrolidone in ethylene glycol to form solution D; injecting solution C into solution D preheated to 155-165℃ under stirring to obtain a mixture; continuously stirring the mixture in an oil bath at 155-165℃ to obtain a reaction solution; naturally cooling the reaction solution to room temperature, adding acetone, centrifuging to collect the precipitate, washing the precipitate alternately with ethanol and cyclohexane to obtain PVP-coated BiTe alloy nanoclusters; and then... Gold nanoclusters were redispersed in anhydrous ethanol, and mercaptopropionic acid was added. The mixture was stirred at 40-50°C, centrifuged, and washed to obtain surface-modified BiTe nanoclusters. The surface-modified BiTe nanoclusters were then dispersed in anhydrous ethanol to obtain an activated BiTe ethanol dispersion. B2. Mercapto-hyaluronic acid was dissolved in phosphate buffer solution at pH 7.2-7.6 to obtain a mercapto-hyaluronic acid mixture. The activated BiTe ethanol dispersion was added dropwise to the mercapto-hyaluronic acid mixture under ultrasonic conditions. After the addition was complete, ultrasonic treatment was continued to obtain a mixture. The mixture was transferred to a dialysis bag and dialyzed in deionized water. The liquid in the dialysis bag was freeze-dried.

2. The method for preparing bladder cancer-targeting nanomedicine according to claim 1, characterized in that, In step S1, the emulsification time under stirring is 2-4 minutes.

3. The method for preparing bladder cancer-targeting nanomedicine according to claim 1, characterized in that, In step S2, the mixture is incubated with shaking at room temperature for 12-14 hours.

4. The method for preparing bladder cancer-targeting nanomedicine according to claim 1, characterized in that, In step A1, the reaction mixture is crystallized and aged at 64-66°C for 18-20 hours.

5. The method for preparing bladder cancer-targeting nanomedicine according to claim 1, characterized in that, In step A2, the reaction time at 25-30℃ under light-protected conditions is 12-18 hours.

6. The method for preparing bladder cancer-targeting nanomedicine according to claim 1, characterized in that, In step B1, the mixture is continuously stirred in an oil bath at 155-165℃ for 3-5 hours.

7. The method for preparing bladder cancer-targeting nanomedicine according to claim 1, characterized in that, In step B2, the ultrasonic treatment continues for 30-40 minutes.

8. A bladder cancer-targeting nanomedicine, characterized in that, The bladder cancer-targeting nanomedicine is prepared by the method according to any one of claims 1-7.

Citation Information

Patent Citations

  • PLGA Gemcitabine sustained-release microsphere and its preparing method

    CN101161239A

  • Preparation method of difunctional mesoporous silicon ball composite targeted drug delivery system

    CN106512023A